2021
DOI: 10.1002/jcla.23783
|View full text |Cite
|
Sign up to set email alerts
|

CYLD deficiency causes auditory neuropathy due to reduced neurite outgrowth

Abstract: Background Auditory neuropathy is a cause of hearing loss that has been studied in a number of animal models. Signal transmission from hair cells to spiral ganglion neurons plays an important role in normal hearing. CYLD is a microtubule‐binding protein, and deubiquitinase involved in the regulation of various cellular processes. In this study, we used Cyld knockout (KO) mice and nerve cell lines to examine whether CYLD is associated with auditory neuropathy. Methods Hearing of Cyld KO mice was studied using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Posttranslational protein modification by ubiquitin provides a plethora of distinct signals that have emerged as key regulators of neuronal activity, including postsynaptic function and plasticity ( Mabb and Ehlers, 2010 ; Kantamneni et al, 2011 ). Ubiquitination by E3 ubiquitin ligases can be reversed by deubiquitinases (DUBs), while deregulation of DUBs has dramatic physiological consequences and causes a variety of diseases such as neurodegeneration or inflammatory disease ( Palazon-Riquelme et al, 2018 ; Yang et al, 2021 ). Targeted deubiquitination via engineered DUBs corrects ion channelopathies caused by trafficking-deficient ion channels ( Kanner et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Posttranslational protein modification by ubiquitin provides a plethora of distinct signals that have emerged as key regulators of neuronal activity, including postsynaptic function and plasticity ( Mabb and Ehlers, 2010 ; Kantamneni et al, 2011 ). Ubiquitination by E3 ubiquitin ligases can be reversed by deubiquitinases (DUBs), while deregulation of DUBs has dramatic physiological consequences and causes a variety of diseases such as neurodegeneration or inflammatory disease ( Palazon-Riquelme et al, 2018 ; Yang et al, 2021 ). Targeted deubiquitination via engineered DUBs corrects ion channelopathies caused by trafficking-deficient ion channels ( Kanner et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mouse hippocampal neurons transfected with CYLD M719V show a significantly increased cytoplasmic localization of transactivator regulatory DNA-binding protein 43 (TDP-43) and decreased axonal length ( Dobson-Stone et al, 2020 ). CYLD deficiency causes impaired fear memory, auditory neuropathy, and cognitive inflexibility ( Li et al, 2021 ; Yang et al, 2021 ; Zajicek et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This observation serves to validate the neurotoxic impact of PTX on PC12 cells (Figure S2B, Supporting Information). [52,53] Accordingly, it was decided to conduct an additional experiment using 10 μM PTX, and the differentiated cells were treated with 10 μM PTX and AR extract, PLGA/AR NPs, and HA-PLGA/AR NPs, respectively. In the case of AR extract and AR PLGA NPs, neurites were about twice as long as when treated with 10 μM PTX and measured about 30-40 μm.…”
Section: Effect Of Ha-plga/ar Nps On Ptx-induced Neurotoxicity In Pc1...mentioning
confidence: 99%
“…In addition, CYLD participates in regulating a large variety of cell processes, including cell cycle progression, cell migration, chemotherapy drug sensitivity, and ciliogenesis (Hu et al, 2022; Ran et al, 2021; Yang & Zhou, 2016; Yang, Chen, et al, 2021). Cyld knockout (KO) mice exhibited exacerbated hearing impairment and cardiac mortality (Xie et al, 2022; Yang, Ma, et al, 2021). Accumulating evidence has revealed that CYLD acts as a pivotal negative regulator of RANK signaling on preosteoclasts, inhibiting ubiquitination of the E3‐ubiquitin ligase TRAF6 and activating downstream signaling pathways (Asagiri & Takayanagi, 2007; Boyle et al, 2003; Durán et al, 2004; Teitelbaum & Ross, 2003).…”
Section: Introductionmentioning
confidence: 99%